Build your Business Website without Coding Experience, A Practical Guide for UMKM - Raswati, Elsa Mundi; Putra, Muhammad Azizsyah; Lantip Nurohman; Muhammad Ghifari; Muhammad Sayyid Farhan; Rita Dewi Risanty; Mujiastuti, Rully; Rosanti, Nurvelly; Hendra; Adharani, Yana (Edumedia Solution, 2026)
In the era of Industrial Revolution 4.0, Small and Medium Enterprises (SMEs) face significant pressure to adapt to digital transformation. However, a major problem persists: many business owners lack the technical skills to build websites and perceive the process as costly and complex, leaving them reliant solely on social media algorithms. To address this gap, a community service program titled